Edukasi Penggunaan Tanaman Herbal Terhadap Penderita Diabetes di Desa Empat Balai, Kampar - Wildan Rasyid; Wirahma Indah Pratiwi; Meiriza Djohari; Deni Anggraini; Enda Mora; M. Almurdani; Ihsan Ikhtiarudin; T. Harpirabi; Jasma Jasma; Tami Tami; Sukma Sukma (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetes mellitus is a public health problem that continues to increase, especially in rural areas that have limited access to modern health services. The use of herbal plants as alternative therapy is increasingly receiving attention because of its abundant availability and relatively low cost. In order to increase public awareness of the importance of prevention and treatment, especially with herbal ingredients for this degenerative disease, there needs to be ongoing counseling, one of which is through community service. This community service activity aims to provide education on the use of herbal plants that have the potential to lower blood sugar levels to the people of Empat Balai Village, Kuok District, Kampar Regency. The activities include counseling, interactive discussions, and demonstrations of the use of local herbal plants such as insulin leaves (Costus igneus), Moringa leaves (Moringa oleifera), Belimbing Wuluh (Averrhoa bilimbi), Pare (Momordica charantia), sambiloto, and mahkota dewa. The research method uses a qualitative approach with counseling techniques and leaflets given to 50 respondents. The results of the study showed an increase in public knowledge or insight about the use of herbal plants for diabetes sufferers with significance (p <0.5). The results of this Community Service activity show the importance of educating the community about managing diabetes naturally and increasing interest in implementing the use of herbs as a treatment support. Therefore, further efforts need to be made to increase insight and prevention related to Diabetes Mellitus by using herbal plants holistically.